Private down under - Patterson, James, 1947- (Patterson, James, 1947- Private novels., 2014)
The employees of the Sydney, Australia office of the investigation company Private are celebrating their office's incorporation when a bloody young man staggers into the building and the agency's caseload suddenly fills up.